Understanding Post-Purchase Regret through Fear of Missing Out: An S-O-R Perspective on Impulse Buying Behavior - Kayla Nazmeen; Amelindha Vania (Universitas Negeri Padang, 2026)
This study aims to examine the effect of Fear of Missing Out (FoMO) on post-purchase regret with impulse buying as a mediating variable among Miniso consumers in Malang City. Drawing on the Stimulus–Organism–Response (SOR) framework, this research employs a quantitative explanatory design, collecting primary data from 150 respondents aged 17–35 years via an online questionnaire and analyzing them using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The results indicate that FoMO has a positive and significant effect on impulse buying and post-purchase regret. At the same time, impulse buying also significantly influences post-purchase regret and mediates the relationship between FoMO and post-purchase regret. These findings reinforce the role of FoMO as a key socio-emotional stimulus driving impulsive purchasing behavior and subsequent evaluative regret in modern retail contexts. Managerially, the study suggests that retailers such as Miniso should optimize promotional strategies by controlling excessive urgency cues (e.g., limited-time offers and scarcity appeals) and strengthening value-based communication to minimize consumer regret while sustaining long-term customer satisfaction and loyalty.